Patient and professional perception of AI in healthcare in Europe - Goldsworthy, Christopher (IE University, 2020)
The success or failure of AI in patient care, treatment or management, hinges on patient and professional acceptance of these digital technologies. However, we still have a limited understanding of how these innovations may be perceived by the professionals and patients who are expected to use them to make important healthcare decisions. This chapter draws together the existing literature to bridge this gap, covering results from multiple surveys and interviews with clinicians across various disciplines, different patient populations and the general public. Two important messages emerge from the literature. Firstly, out of all the hopes and concerns, both patients and professionals consistently agree that AI healthcare innovations should be fully integrated within healthcare systems and should complement the work of clinicians, instead of replacing them. Secondly, studies in this area are still relatively limited, particularly regarding patients’ perspectives. There is a pressing need for the development of comprehensive, largescale studies to understand patients’ needs, expectations and concerns when it comes to AI applications. The results will be essential for developing a successful and patient-centred medical AI innovation pathway.
Keywords: Artificial intelligence;AI healthcare;Healthcare innovations;AI applications; Artificial intelligence; AI healthcare; Healthcare innovations; AI applications